![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm
a) x² - 3 = 22
=> x² = 25
=> x = + 5
Vậy x = + 5
b) 2x³ + 5 = -11
2x³ = -16
x³ = -8
x = -2
Vậy x = -2
c) ( x + 2 )² = 81
=> x + 2 = 9
=> x = 7
Vậy x = 7
d) ( 2x + 1 )² = 25
=> 2x + 1 = 5
=> 2x = 4
=> x = 2
Vậy x = 2
e) 5x + 2 = 625
5x = 623 ( vô lí )
g) ( 2x - 3 )² = 36.
=> 2x - 3 = 6
=> 2x = 9
=> x = 4,5
Vậy x = 4,5
h) ( 2x - 1 )³ = -8
=> 2x - 1 = -2
=> 2x = -1
=> x = -1/2
Vậy x = -1/2
i) ( x - 1 )x + 2 = ( x - 1 )x + 6
=> [ (x - 1 )x - ( x - 1 )x ] = 6 - 2
=> 0 = 4 ( vô lí )
Vậy x thuộc rỗng.
k) x² + x = 0
=> x( x + 1 ) = 0
=> x = 0 hoặc x + 1 = 0
=> x = 0 hoặc x = -1
Vậy x = 0 hoặc x = -1
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =>1/3:x=3/5-2/3=9/15-10/15=-1/15
=>x=-1/3:1/15=5
b: \(\Leftrightarrow x\cdot\dfrac{2}{3}-3=\dfrac{2}{5}\cdot\left(-10\right)=-4\)
=>x*2/3=-1
=>x=-3/2
c: =>2x+1=4 hoặc 2x+1=-4
=>x=3/2 hoặc x=-5/2
h: =>x-3=4
=>x=7
g: =>2x-1=3
=>2x=4
=>x=2
f: \(\Leftrightarrow x\cdot\left(\dfrac{3}{2}-\dfrac{7}{3}\right)=\dfrac{3}{2}-\dfrac{2}{3}\)
=>x*-5/6=5/6
=>x=-1
d: =>|2x-1|=3
=>2x-1=3 hoặc 2x-1=-3
=>x=-1 hoặc x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
2 . 1/8 = 2/2.4 + 2/4.6 + ...+ 2/((2x -2).2x)
1/4 = 4-2/2.4 + 6-4/4.6 + ... + 2x-(2x-2)/(2x-2)+2x
1/4 = 1/2 - 1/4 + 1/4 - 1/6 + 1/6 - 1/8 + ... + 1/2x -2 - 1/2x
1/4 = 1/2 - 1/2x
1/4 = 2x-2/2.2x
Tự làm tiếp nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
Đặt \(A=\frac{1}{2.4}+\frac{1}{4.6}+...+\frac{1}{\left(2x-2\right).2x}\)
\(\Rightarrow A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{6}+...+\frac{1}{2x-2}-\frac{1}{2x}\right)\)
\(\Rightarrow A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2x}\right)\)
\(\Rightarrow\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2x}\right)=\frac{1}{8}\)
\(\Rightarrow\frac{1}{2}-\frac{1}{2x}=\frac{1}{4}\)
\(\Rightarrow\frac{1}{2x}=\frac{1}{4}\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=2\)
Đặt \(A=\frac{1}{2.4}+\frac{1}{4.6}+...+\frac{1}{\left(2x-2\right).2x}\)
\(\Rightarrow A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{6}+...+\frac{1}{2x-2}-\frac{1}{2x}\right)\)
\(\Rightarrow A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2x}\right)\)
\(\Rightarrow\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2x}\right)=\frac{1}{8}\)
\(\Rightarrow\frac{1}{2}-\frac{1}{2x}=\frac{1}{4}\)
\(\Rightarrow\frac{1}{2x}=\frac{1}{4}\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{2.4}+\frac{1}{4.6}+...+\frac{1}{\left[\left(2x-2\right).2x\right]}=\frac{1}{8}\)
\(\Rightarrow\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{6}+...+\frac{1}{2x-2}-\frac{1}{2x}\right)=\frac{1}{8}\)
\(\Rightarrow\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2x}\right)=\frac{1}{8}\)
\(\Rightarrow\frac{1}{2}-\frac{1}{2x}=\frac{1}{8}:\frac{1}{2}\)
\(\Rightarrow\frac{1}{2}-\frac{1}{2x}=\frac{1}{4}\)
\(\Rightarrow\frac{1}{2x}=\frac{1}{2}-\frac{1}{4}\)
\(\Rightarrow\frac{1}{2x}=\frac{1}{4}\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2: 12-10x=25-30x
=>20x=13
=>x=13/20
3: \(3\left(2x+3\right)-2\left(4x-5\right)=10x+21\)
=>6x+9-8x+10=10x+21
=>10x+21=-2x+19
=>12x=-2
=>x=-1/6
4: \(\Leftrightarrow25x-15-6x+12=11-5x\)
=>19x-3=11-5x
=>24x=14
=>x=7/12
5: \(\Leftrightarrow8-12x-5+10x=4-6x\)
=>4-6x=-2x+3
=>-4x=-1
=>x=1/4
6: \(\Leftrightarrow32x-24-6+9x=13-40x\)
=>41x-30=13-40x
=>81x=43
=>x=43/81
7: \(\Leftrightarrow10x-5+20x=5x-11\)
=>30x-5=5x-11
=>25x=-6
=>x=-6/25
![](https://rs.olm.vn/images/avt/0.png?1311)
1) ( 2x + 1 )2 = 25
=> ( 2x + 1 )2 = 52
=> 2x + 1 = 5 hoặc 2x + 1 = -5
=> 2x = 4 hoặc 2x = -6
=> x = 2 hoặc x = -3
2) 5x+2 = 625
=> 5x+2 = 54
=> x + 2 = 4
=> x = 2
3) ( 2x - 3 )2 = 36
=> ( 2x - 3 )2 = 62
=> 2x - 3 = 6 hoặc 2x - 3 = -6
=> 2x = 9 hoặc 2x = -3
=> x = 9/2 hoặc x = -3/2
4) ( 2x - 1 )3 = -8
=> ( 2x - 1 )3 = ( -2 )3
=> 2x - 1 = -2
=> 2x = -1
=> x = -1/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{-2}{3}x+\frac{1}{5}=\frac{1}{10}\)
\(\Leftrightarrow\frac{-2}{3}x=\frac{1}{10}-\frac{1}{5}\)
\(\Leftrightarrow\frac{-2}{3}x=\frac{-1}{10}\)
\(\Leftrightarrow x=\frac{-1}{10}\div\frac{-2}{3}\)
\(\Leftrightarrow x=\frac{3}{20}\)
\(2\left(\dfrac{1}{2}-2x\right)^2=8\)
\(\Rightarrow\left(\dfrac{1}{2}-2x\right)^2=4=2^2\)
\(\Rightarrow\left[{}\begin{matrix}\dfrac{1}{2}-2x=2\\\dfrac{1}{2}-2x=-2\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=\dfrac{1}{2}-2\\2x=\dfrac{1}{2}+2\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=-\dfrac{3}{2}\\2x=\dfrac{5}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{3}{4}\\x=\dfrac{5}{4}\end{matrix}\right.\)